Battery aluminum foil, method for producing same, secondary battery, and electric device
By adjusting the Fe and Si content in the aluminum foil of lithium-ion battery, controlling the Fe/Si weight ratio and the α-phase structure content, the problem that the existing aluminum foil of battery cannot improve the tensile strength and elongation at the same time is solved, and the effects of high strength, high elongation and improving brittleness are achieved.
Patent Information
- Application Number
- CN202410138173.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-31
- Publication Date
- 2025-04-18
AI Technical Summary
While improving the mechanical properties of existing lithium-ion batteries, the aluminum foil cannot simultaneously improve the tensile strength and elongation, resulting in greater brittleness of the battery pole.
By adjusting the Fe and Si content of the battery aluminum foil, the Fe/Si weight ratio is controlled between 1.2 and 1.5, the content of the α-phase structure is increased, so that the second phase is more diffuse, fine and evenly distributed, thereby improving the tensile strength and elongation of the aluminum foil.
The high strength and elongation of the battery aluminum foil are achieved, the brittleness of the battery electrode sheet is improved, the anti-wrinkle ability is improved, the manufacturing process is simplified, and the production cost is reduced.
Smart Images

Figure CN119843109A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a battery aluminum foil and a manufacturing method thereof, a secondary battery, and an electrical device. Background Art
[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As secondary batteries have made great progress, higher requirements have been put forward for their energy density, cycle performance and safety performance. The thickness of the battery foil, one of the core components of the electrode plate, also needs to be further reduced to increase the surface area per unit volume. However, this puts higher requirements on the strength and elongation of the battery foil.
[0003] At present, the lithium-ion battery aluminum foil industry mainly uses 1060 / 1070 alloy battery aluminum foil with a Fe / Si weight ratio greater than 2 in mass production. The improvement of mechanical properties mainly relies on cold rolling work hardening and adding copper content to adjust. Under the condition of ensuring the basic elongation of ≥3%, the strength improvement is limited to only 220MPa, and it is impossible to improve both tensile strength and elongation at the same time. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a battery aluminum foil having both high strength and high elongation and a method for manufacturing the same, a secondary battery including the battery aluminum foil, and an electrical device.
[0005] A first aspect of the present application provides a battery aluminum foil containing Fe and Si. Based on the total weight of the battery aluminum foil, the Fe content is 0.4wt% to 0.65wt%, the Si content is 0.25wt% to 0.54wt%, and the weight ratio of Fe to Si, Fe / Si, is 1.2 to 1.5.
[0007] In the embodiments of the present application, by adopting a battery aluminum foil having the composition described above, the second phase of the aluminum foil presents a more dispersed, fine and uniform distribution state, thereby being able to disperse the internal stress of the material and improve the tensile strength and elongation of the material; in addition, the pinholes of the obtained battery aluminum foil reach the level of general battery foil, which can effectively improve the brittleness of the battery electrode when used in secondary batteries and improve the wrinkle resistance of the battery aluminum foil.
[0008] Specifically, there are three structural forms in the second phase of the aluminum foil of the present application: α phase, β phase and θ phase. Among them, the α phase structure is easier to break during the material processing process; the β phase structure is a rod-shaped structure, which is not easy to deform, and its fragmentation ability during the material processing process is poor. By making the second phase of the aluminum foil of the present application present more α phase structure, based on the easy-to-break nature of the α phase structure, the second phase can be made to present a more dispersed, fine and uniform distribution state during the material processing process, thereby dispersing the internal stress of the aluminum foil material and improving the tensile strength and elongation of the aluminum foil.
[0009] Further optionally, in the aluminum foil of the present application, the main composition of the α phase and the β phase can be an AlFeSi structure. The difference is that the number of Fe and Si atoms in the structure is different. The Fe / Si atomic ratio is greater than or equal to 1 for the α phase, and less than 1 for the β phase. The θ phase is composed of an AlFe structure. By regulating the weight ratio of Fe to Si Fe / Si in the aluminum foil of the present application, the second phase can contain more α phase, such as the AlFeSi structure with a Fe / Si atomic ratio greater than or equal to 1. The AlFeSi structure with a Fe / Si atomic ratio greater than or equal to 1 has the easy-to-break property of the α phase structure described in the present application, and can make the second phase present a more dispersed, fine, and uniform distribution state during the material processing, which is beneficial to improve the strength and elongation of the aluminum foil.
[0010] In any embodiment, based on the total weight of the battery aluminum foil, the content of Si is 0.267wt% to 0.54wt%. By making the content of each component in the battery aluminum foil within the above range, the strength and elongation can be further improved.
[0011] In any embodiment, at least part of the second phase of the aluminum foil has a size of less than 3 μm. In any embodiment, the second phase less than 3 μm may account for 60-100% of all the second phases, such as 60% to 100%, specifically 80% to 100%.
[0012] In the present application, the morphology of the second phase is generally random, as shown in the attached Figure 1 The light-colored part in the middle is shown. The size can be considered as the diameter of the circumscribed circle of the second phase structure, which can be obtained by observing and measuring an aluminum foil with a thickness of 13 μm under an electron microscope (ZEISS).
[0013] By making the size of at least part of the second phase of the aluminum foil within the above range, the second phase is in a dispersed, fine and uniform distribution state, which can further improve the strength and elongation of the aluminum foil.
[0014] In any embodiment, the second phase of the aluminum foil contains 5 wt % to 10 wt % of AlFeSi structure and 4 wt % to 9 wt % of AlFe structure.
[0015] The content of the phase structure in the second phase is determined using an electron backscatter diffraction (EBSD) method. Specifically, a cross section of an aluminum foil having a thickness of 13 μm is observed using a backscattered electron fiberscope, and the AlFeSi and AlFe crystal structures and the content of the crystal structures are determined by the electron pattern reflected from the sample surface.
[0016] As mentioned above, the AlFeSi structure contained in the second phase of the aluminum foil is an α-phase and β-phase structure, and the AlFe structure is a θ-phase structure. The content of the AlFeSi structure contained in the second phase of the aluminum foil of the present application is increased compared to the existing aluminum foil, and thus the content of the α-phase is also increased. Based on the property that the α-phase structure is easily broken during the material processing process, by making the second phase of the battery aluminum foil contain 5wt% to 10wt% of the AlFeSi structure and 4wt% to 9wt% of the AlFe structure, the second phase of the battery aluminum foil material finally obtained is more dispersed, fine, and evenly distributed, thereby dispersing the internal stress of the material and improving the tensile strength and elongation of the material.
[0017] In any embodiment, based on the total weight of the battery aluminum foil, the battery aluminum foil also contains less than or equal to 0.03wt% Cu. If the copper content is too high, it will form a composite second phase with sendust etc., thereby increasing the size of the second phase in the battery aluminum foil, which is not conducive to improving the elongation.
[0018] In any embodiment, based on the total weight of the battery aluminum foil, the battery aluminum foil further contains 0.015wt% to 0.05wt% Ti, and optionally 0.025wt% to 0.045wt% Ti. By making the battery aluminum foil contain the Ti element within the above range, the elongation of the battery aluminum foil can be further improved.
[0019] In any embodiment, the battery aluminum foil further contains Mn, Mg and Zn, and based on the total weight of the battery aluminum foil, the content of Mn is 0<Mn≤0.05wt%, the content of Mg is 0<Mg≤0.05wt%, and the content of Zn is 0<Zn≤0.05wt%. Mn, Mg and Zn, as elements contained in the aluminum ingot used as the raw material for producing the battery aluminum foil, will form a composite second phase with iron silicon aluminum and the like, thereby increasing the size of the second phase in the battery aluminum foil, which is not conducive to the improvement of the elongation. By controlling the content of Mn, Mg and Zn within the range, the production cost caused by purifying trace Mn, Mg and Zn elements can be reduced while maintaining the high strength and high elongation of the battery aluminum foil.
[0020] In any embodiment, the battery aluminum foil has a thickness of 12 μm to 15 μm.
[0021] Generally, in the manufacturing process of battery aluminum foil, the component segregation generated in the casting process can be alleviated by performing an annealing process on the material, so that the internal composition of the material is more uniform. In the embodiment of the present application, by making the thickness of the battery aluminum foil within the above range, the aluminum foil is thinner, and even without annealing, the uneven composition in the material can be reduced, so that the obtained battery aluminum foil can achieve high strength and high elongation.
[0022] In any embodiment, the roughness of the battery aluminum foil is 0.1 μm to 0.3 μm.
[0023] By making the roughness of the battery aluminum foil within the above range, the structural defects on the surface of the battery aluminum foil can be reduced, so that the battery aluminum foil has high mechanical properties.
[0024] In any embodiment, the tensile strength of the aluminum foil is 200MPa-300MPa. The tensile strength of the aluminum foil is tested by a tensile machine under the condition of a gauge length of 50±2mm and a tensile speed of 5±0.2mm / min. The size of the sample is 150±1mm in length, 15±0.1mm in width, and 0.013mm±0.001 in thickness. The sample is fixed to the test fixture of the tensile machine, and the tensile curve is measured. The tensile strength of the battery aluminum foil is calculated by the maximum tensile force in the tensile curve.
[0025] In any embodiment, the elongation at break of the aluminum foil is 3.2%-7%. The tensile strength of the aluminum foil is tested by a tensile machine under the condition of a gauge length of 50±2mm and a tensile speed of 5±0.2mm / min. The size of the sample is 150±1mm in length, 15±0.1mm in width, and 0.013mm±0.001 in thickness. The sample is fixed to the test fixture of the tensile machine, and the elongation at break is divided by the length before stretching. The ratio is taken as the elongation at break.
[0026] The aluminum foil has both good tensile strength and excellent elongation at break. Using it as a current collector can effectively improve the flexibility of the pole piece and reduce the probability of brittle fracture of the pole piece, providing a material basis for improving the compaction density of the pole piece and the energy efficiency of the battery.
[0027] The second aspect of the present application also provides a method for manufacturing a battery aluminum foil, wherein the battery aluminum foil is formed by heating and smelting a smelting raw material in a smelting furnace, and then casting and rolling.
[0028] The composition of the smelting raw material is as follows: based on the total weight of the smelting raw material, the content of Fe is 0.4wt% to 0.65wt%, the content of Si is 0.25wt% to 0.54wt%, and the weight ratio of Fe to Si (Fe / Si) is 1.2 to 1.5.
[0029] Therefore, through the manufacturing method of the present application, a battery aluminum foil with high strength and high elongation can be obtained.
[0030] In any embodiment, the composition of the smelting raw material is: based on the total weight of the smelting raw material, the content of Si is 0.267wt% to 0.54wt%. By controlling the content of Si within the range, the second phase in the battery aluminum foil can be more concentratedly presented as a dispersed, fine, and evenly distributed AlFeSi phase structure, thereby dispersing the internal stress of the material and further improving the tensile strength and elongation of the material. In addition, when the battery aluminum foil is used in secondary batteries, it can effectively improve the brittleness of the battery pole piece and improve the wrinkle resistance of the aluminum foil.
[0031] In any embodiment, based on the total weight of the smelting raw material, the smelting raw material also contains less than or equal to 0.03wt% Cu. Cu, as an element contained in the aluminum ingot of the raw material for producing battery aluminum foil, will form a composite second phase with sendust and the like, thereby increasing the size of the second phase in the battery aluminum foil, which is not conducive to improving the elongation. By controlling the Cu content within the range, the production cost caused by purifying trace Cu elements can be reduced while maintaining the high strength and high elongation of the battery aluminum foil.
[0032] In any embodiment, based on the total weight of the smelting raw material, the smelting raw material further contains 0.015wt% to 0.05wt% Ti, and optionally 0.025wt% to 0.045wt% Ti. By making the content of Ti within this range, it can help to refine the grains in the second phase of the battery aluminum foil, make the second phase in the battery aluminum foil more uniform and dispersed, reduce the internal stress of the material, and improve the strength and elongation of the material.
[0033] In any embodiment, the smelting raw material further contains Mn, Mg and Zn, and based on the total weight of the smelting raw material, the content of Mn is 0<Mn≤0.05wt%, the content of Mg is 0<Mg≤0.05wt%, and the content of Zn is 0<Zn≤0.05wt%. Mn, Mg and Zn, as elements contained in the aluminum ingot of the raw material for producing battery aluminum foil, will form a composite second phase with iron, silicon and aluminum, thereby increasing the size of the second phase in the battery aluminum foil, which is not conducive to the improvement of elongation. By controlling the content of Mn, Mg and Zn within the range, the production cost caused by purifying trace copper elements can be reduced while maintaining the high strength and high elongation of the battery aluminum foil.
[0034] In any embodiment, the manufacturing method includes a cold rolling process, and the annealing process may not be performed in the middle of the cold rolling process. Normally, in the manufacturing process of battery aluminum foil, the component segregation of the material produced during the casting and rolling process can be alleviated by performing an annealing process on the material, making the internal composition of the material more uniform. However, the second phase of the aluminum foil of the present application is in a dispersed, fine, and uniformly distributed state. When the annealing process is performed, the second phase in the above state is prone to remelting, resulting in a decrease in the degree of refinement and an increase in size, which affects the performance of the aluminum foil. Based on this, the present application can reduce the impact of uneven composition on material performance by controlling the thickness of the aluminum foil material even if the annealing process is not performed.
[0035] In any embodiment, the method for manufacturing the battery aluminum foil comprises the following steps:
[0036] I. Melting process: When the temperature of the aluminum alloy melt reaches 710℃~740℃, refining and slag removal, grain refinement, degassing and slag removal, and filtration are carried out to obtain an aluminum alloy melt.
[0037] II. Casting step, the filtered aluminum alloy melt is put into a casting and rolling mill to cast and roll into a cast billet;
[0038] III. a cold rolling step of cold rolling the cast billet;
[0039] IV. trimming process to obtain aluminum foil blank;
[0040] V. Foil rolling process, rolling the aluminum foil blanks into aluminum foil coils;
[0041] VI. Aluminum foil slitting process, slitting the aluminum foil roll to obtain battery aluminum foil.
[0042] In any embodiment, the method for manufacturing battery aluminum foil, wherein, in the casting and rolling process, the filtered aluminum alloy melt is put into a casting and rolling machine for continuous casting and rolling into a cast-rolled billet of, for example, 5mm to 9mm, optionally 6mm to 7mm. In the cold rolling process, the cast-rolled billet is cold rolled until the thickness is, for example, 0.15mm to 0.3mm, optionally 0.2mm to 0.25mm, and the number of cold rolling passes is, for example, 3-6 times, preferably 5 times. In the trimming process, trimming can be performed at a thickness of, for example, 0.8mm to 1.5mm and / or a thickness of 0.2mm to 0.25mm to obtain an aluminum foil billet. In the foil rolling process, the trimmed aluminum foil blank is subjected to rough rolling, intermediate rolling and finish rolling in sequence to form an aluminum foil coil with a thickness of 0.01mm to 0.02mm, optionally 0.01mm to 0.015mm. The number of rolling passes is not particularly limited, and can be selected as a total of 5-9 passes, and can further be selected as 6 to 7 passes.
[0043] The second phase of the battery aluminum foil obtained by the manufacturing method of the present application presents a more dispersed, fine, and uniform distribution state, thereby being able to disperse the internal stress of the material and improve the tensile strength and elongation of the material; in addition, the pinholes of the obtained battery aluminum foil reach the level of general battery foils, which can effectively improve the brittleness of the battery pole piece and improve the anti-wrinkling ability of the battery aluminum foil when used in secondary batteries. In addition, since annealing treatment is not required, the manufacturing method of the present application has the advantages of short process flow, high production efficiency, low energy consumption, and low cost.
[0044] The third aspect of the present application provides a battery pole piece, which includes the battery aluminum foil of the first aspect of the present application.
[0045] The pole piece has improved brittleness and can achieve a higher ultimate compaction density, which is conducive to further improving the energy density of the battery.
[0046] In any embodiment, the compacted density of the battery electrode is 3.5 g / cm 3 The bending times of the battery electrode sheet are greater than or equal to 3 times; the bending times of the battery electrode sheet are tested by rolling method, the battery electrode sheet is cut into test specimens of 15 cm × 2.5 cm in size, and a 2 kg rolling roller is used to roll the bent and folded electrode sheet. If there is no light transmission or fracture at the bending part of the electrode sheet, the electrode sheet is folded in reverse and rolled, and the number of rolling times at which light transmission or fracture appears at the folded part of the electrode sheet is taken as the bending times of the battery electrode sheet.
[0047] In any embodiment, the compacted density of the battery electrode is 3.5 g / cm 3 When the battery electrode has a fracture elongation greater than 2.1%.
[0048] A fourth aspect of the present application provides a secondary battery, which includes the battery electrode according to the third aspect of the present application.
[0049] A fifth aspect of the present application provides an electrical device, which includes the secondary battery of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is the second phase structure of the battery aluminum foil under a microscope according to one embodiment of the present application.
[0051] Figure 2 This is the relationship between the elongation and tensile strength of the battery aluminum foil according to one embodiment of the present application.
[0052] Figure 3 is a schematic diagram of an embodiment of a secondary battery of the present application;
[0053] Figure 4 is an exploded schematic diagram of an embodiment of a secondary battery of the present application;
[0054] Figure 5 is a schematic diagram of an embodiment of a battery module of the present application;
[0055] Figure 6 is a schematic diagram of an embodiment of a battery pack of the present application; Figure 7 yes Figure 6 An exploded schematic diagram of an embodiment of a battery pack is shown; Figure 8 It is a schematic diagram of one embodiment of an electric device including the secondary battery of the present application as a power source.
[0056] Description of reference numerals:
[0057] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION
[0058] The following is a detailed description of the battery aluminum foil, the secondary battery containing the battery aluminum foil, the electric device and the manufacturing method thereof of the present application. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0059] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0060] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0061] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0062] If not otherwise specified, all steps of the present application may be performed sequentially or randomly, and may be performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0063] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0064] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0065] For the sizes or particle diameters of various particles, they can be measured and calculated to show the average size of a group. The methods used include the mode diameter showing the maximum value of the distribution, the median diameter corresponding to the central value of the integral distribution curve, and various average diameters (digital average, length average, area average, mass average, volume average, etc.).
[0066] In the existing battery aluminum foil, by adjusting the grain size and the proportion of rolling texture, the alloy is mainly FeAl 3 In addition, the manufacturing process of battery aluminum foil includes annealing process, which has a long production cycle. 3 The phase foil is hard and brittle and not easy to break during the rolling process, and the battery aluminum foil has a high pinhole density.
[0067] In order to improve the performance of battery aluminum foil, by adjusting the content of the main elements in the alloy, the refinement degree of the second phase in the battery aluminum foil can be controlled to make it sufficiently dispersed, small and uniform, and to disperse its stress concentration, thereby achieving an increase in its strength and elongation. Based on this, the embodiment of the present application provides a 1200 alloy formula with a Fe / Si ratio of 1.2 to 1.5, and prepares a high tensile strength and high elongation battery aluminum foil through casting, cold rolling, and foil rolling processes, and eliminates the traditional intermediate annealing process.
[0068] Based on this, the present application proposes a battery aluminum foil having both high strength and high elongation, a secondary battery including the battery aluminum foil, an electric device and a manufacturing method thereof. Now, each of them will be described in detail.
[0069] [Battery aluminum foil]
[0070] The battery aluminum foil of the embodiment of the present application contains Fe and Si. Based on the total weight of the battery aluminum foil, the Fe content is 0.4wt% to 0.65wt%, the Si content is 0.25wt% to 0.54wt%, and the weight ratio of Fe to Si, Fe / Si, is 1.2 to 1.5.
[0071] In some embodiments, the Fe content may be 0.4wt%, 0.41wt%, 0.42wt%, 0.43wt%, 0.44wt%, 0.45wt%, 0.46wt%, 0.47wt%, 0.48wt%, 0.49wt%, 0.50wt%, 0.51wt%, 0.52wt%, 0.53wt%, 0.54wt%, 0.55wt%, 0.56wt%, 0.57wt%, 0.58wt%, 0.59wt%, 0.60wt%, 0.61wt%, 0.62wt%, 0.63wt%, 0.64wt% or 0.65wt%, or a range between any two of the above values.
[0072] In some embodiments, the Si content may be 0.25wt%, 0.26wt%, 0.27wt%, 0.28wt%, 0.29wt%, 0.30wt%, 0.31wt%, 0.32wt%, 0.33wt%, 0.34wt%, 0.35wt%, 0.36wt%, 0.37wt%, 0.38wt%, 0.39wt%, 0.40wt%, 0.41wt%, 0.42wt%, 0.43wt%, 0.44wt%, 0.45wt%, 0.46wt%, 0.47wt%, 0.48wt%, 0.49wt%, 0.50wt%, 0.51wt%, 0.52wt%, 0.53wt% or 0.54wt%, or a range between any two of the above values.
[0073] In some embodiments, the weight ratio of the Fe to the Si may be 1.2, 1.3, 1.4 or 1.5.
[0074] In the embodiments of the present application, by adopting a battery aluminum foil having the composition described above, the second phase of the aluminum foil presents a more dispersed, fine and uniform distribution state, thereby being able to disperse the internal stress of the material and improve the tensile strength and elongation of the material; in addition, the pinholes of the obtained battery aluminum foil reach the level of general battery foil, which can effectively improve the brittleness of the battery electrode when used in secondary batteries and improve the wrinkle resistance of the battery aluminum foil.
[0075] Specifically, there are three structural forms in the second phase of the aluminum foil of the present application: α phase, β phase and θ phase. Among them, the α phase structure is easier to break during the material processing process; the β phase structure presents a rod-like structure, which is not easy to deform, and its fragmentation ability in the material processing process is poor compared with the θ phase. By making the second phase of the aluminum foil of the present application mainly present an α phase structure, based on the easy-to-break nature of the α phase structure, the second phase can be made to present a more dispersed, fine and uniform distribution state during the material processing process, thereby dispersing the internal stress of the aluminum foil material and improving the tensile strength and elongation of the aluminum foil.
[0076] Further optionally, in the aluminum foil of the present application, the main composition of the α phase and the β phase can be an AlFeSi structure. The difference is that the number of Fe and Si atoms in the structure is different. The Fe / Si atomic ratio is greater than or equal to 1 for the α phase, and less than 1 for the β phase. The θ phase is composed of an AlFe structure. By regulating the weight ratio of Fe to Si Fe / Si in the aluminum foil of the present application, the second phase can contain more α phase, such as the AlFeSi structure with a Fe / Si atomic ratio greater than or equal to 1. The AlFeSi structure with a Fe / Si atomic ratio greater than or equal to 1 has the easy-to-break property of the α phase structure described in the present application, and can make the second phase present a more dispersed, fine, and uniform distribution state during the material processing, which is beneficial to improve the strength and elongation of the aluminum foil.
[0077] In any embodiment, based on the total weight of the battery aluminum foil, the content of Si is 0.267wt% to 0.54wt%. By making the content of each component in the battery aluminum foil within the above range, the strength and elongation can be further improved.
[0078] In any embodiment, the size of the second phase of the aluminum foil portion is less than 3 μm. In the present application, the morphology of the second phase is generally random, as shown in the attached Figure 1 The light-colored part in the middle is shown. The size can be considered as the diameter of the circumscribed circle of the second phase structure, which can be obtained by observing and measuring an aluminum foil with a thickness of 13 μm under an electron microscope (ZEISS).
[0079] In any embodiment, the size of at least part of the second phase of the aluminum foil is less than 3 μm. In any embodiment, the proportion of the second phase less than 3 μm in all second phases can be 60-100%, such as 60% to 100%, specifically 80% to 100%. In any embodiment, the proportion of the second phase less than 3 μm in all second phases can be 60%, 70%, 80%, 90%, 100% or any range of values therebetween. In any embodiment, the proportion of the second phase less than 3 μm in all second phases can be 100%.
[0080] By making the size of the second phase of the aluminum foil part within the above range, the second phase is in a dispersed, fine and uniform distribution state, which can further improve the strength and elongation of the aluminum foil.
[0081] In any embodiment, the second phase of the aluminum foil contains 5 wt % to 10 wt % of AlFeSi structure and 4 wt % to 9 wt % of AlFe structure.
[0082] In some embodiments, the second phase contains 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt% of AlFeSi structure; in some embodiments, the second phase contains 5wt%, 6wt%, 7wt%, 8wt% or 9wt% of AlFe structure, or a range between any two of the above values.
[0083] As mentioned above, the AlFeSi structure contained in the second phase of the aluminum foil is an α-phase and β-phase structure, and the AlFe structure is a θ-phase structure. The content of the AlFeSi structure contained in the second phase of the aluminum foil of the present application is increased compared to the existing aluminum foil, and thus the content of the α-phase is also increased. Based on the property that the α-phase structure is easily broken during the material processing process, by making the second phase of the battery aluminum foil contain 5wt% to 10wt% of the AlFeSi structure and 4wt% to 9wt% of the AlFe structure, the second phase of the battery aluminum foil material finally obtained is more dispersed, fine, and evenly distributed, thereby dispersing the internal stress of the material and improving the tensile strength and elongation of the material.
[0084] In any embodiment, the battery aluminum foil further contains less than or equal to 0.03 wt % of Cu based on the total weight of the battery aluminum foil.
[0085] In some embodiments, the battery aluminum foil further contains less than or equal to 0.03 wt %, 0.02 wt % or 0.01 wt % of Cu, or a range between any two of the above values.
[0086] Cu is an element contained in the aluminum ingots used as raw materials for producing battery aluminum foil. If the copper content is too high, it will form a composite second phase with iron, silicon, and aluminum, which will increase the size of the second phase in the battery aluminum foil, which is not conducive to improving the elongation. By controlling the Cu content within the above range, the production cost caused by purifying trace copper elements can be reduced while maintaining the high strength and high elongation of the battery aluminum foil.
[0087] In some embodiments, based on the total weight of the battery aluminum foil, the battery aluminum foil further contains 0.015 wt % to 0.05 wt % of Ti, and optionally further contains 0.025 wt % to 0.045 wt % of Ti.
[0088] In some embodiments, based on the total weight of the battery aluminum foil, the battery aluminum foil further contains 0.015wt%, 0.02wt%, 0.025wt%, 0.03wt%, 0.035wt%, 0.04wt%, 0.045wt% or 0.05wt% Ti, or a range between any two of the above values.
[0089] By making the Ti content within this range, it can help to refine the grains in the second phase of the battery aluminum foil, make the second phase in the battery aluminum foil more uniform and dispersed, reduce the internal stress of the material, and improve the strength and elongation of the material.
[0090] In some embodiments, the battery aluminum foil further contains Mn, Mg and Zn, and based on the total weight of the battery aluminum foil, the content of Mn is 0<Mn≤0.05wt%, the content of Mg is 0<Mg≤0.05wt%, and the content of Zn is 0<Zn≤0.05wt%.
[0091] Mn, Mg and Zn, as elements contained in aluminum ingots used as raw materials for producing battery aluminum foil, will form a composite second phase with iron, silicon and aluminum, thereby increasing the size of the second phase in the battery aluminum foil. By controlling the content of Mn, Mg and Zn within the above range, the production cost caused by purifying trace amounts of Mn, Mg and Zn elements can be reduced while maintaining the high strength and high elongation of the battery aluminum foil.
[0092] In some embodiments, the thickness of the battery aluminum foil is 10 μm to 15 μm, which can be 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm, or a range between any two of the above values.
[0093] Generally, in the manufacturing process of battery aluminum foil, the component segregation generated in the casting process can be alleviated by performing an annealing process on the material, so that the internal composition of the material is more uniform. In the embodiment of the present application, by making the thickness of the battery aluminum foil within the above range, the aluminum foil is thinner, and even without annealing, the uneven composition in the material can be reduced, so that the obtained battery aluminum foil can achieve high strength and high elongation.
[0094] In some embodiments, the roughness of the battery aluminum foil is 0.1 μm to 0.3 μm, which can be 0.1 μm, 0.2 μm or 0.3 μm, or a range between any two of the above values.
[0095] By setting the roughness of the battery aluminum foil within the above range, microscopic defects on the material surface can be reduced, thereby ensuring good mechanical properties of the battery aluminum foil.
[0096] [Manufacturing method of battery aluminum foil]
[0097] In one embodiment of the present application, a method for manufacturing battery aluminum foil is provided, wherein the battery aluminum foil is formed by heating and smelting a smelting raw material in a smelting furnace and then casting and rolling it, and the composition of the smelting raw material is: based on the total weight of the smelting raw material, the Fe content is 0.4wt% to 0.65wt%, the Si content is 0.25wt% to 0.54wt%, and the weight ratio of the Fe to the Si, Fe / Si, is 1.2 to 1.5.
[0098] It should be noted that the smelting raw materials in the implementation mode of the present application will be lost during the smelting process, resulting in changes in the content of each element and the content ratio of each element within a small error (±0.1%), but this small change will not affect the material properties of the battery aluminum foil of the present application.
[0099] According to the manufacturing method of the present application, the second phase of the obtained battery aluminum foil presents a more dispersed, fine and uniform distribution state, thereby being able to disperse the internal stress of the material and improve the tensile strength and elongation of the material; in addition, the pinholes of the obtained battery aluminum foil reach the level of general battery foil, which can effectively improve the brittleness of the battery electrode when used in secondary batteries and improve the wrinkle resistance of the battery aluminum foil.
[0100] As mentioned above, there are three structural forms in the second phase of the aluminum foil of the present application: α phase, β phase and θ phase. Among them, the α phase structure is easier to break during the material processing, while the β phase structure presents a rod-like structure and is not easy to deform. It and the θ phase have poor fragmentation capabilities during the material processing. By making the second phase of the aluminum foil of the present application mainly present an α phase structure, based on the easy-to-break nature of the α phase structure, the second phase can be made to present a more dispersed, fine and uniform distribution state during the material processing, thereby dispersing the internal stress of the aluminum foil material and improving the tensile strength and elongation of the aluminum foil.
[0101] Further optionally, in the aluminum foil of the present application, the main composition of the α phase and the β phase can be an AlFeSi structure. The difference is that the number of Fe and Si atoms in the structure is different. The Fe / Si atomic ratio is greater than or equal to 1 for the α phase, and less than 1 for the β phase. The θ phase is composed of an AlFe structure. By regulating the weight ratio of Fe to Si Fe / Si in the aluminum foil of the present application, the second phase can contain more α phase, such as the AlFeSi structure with a Fe / Si atomic ratio greater than or equal to 1. The AlFeSi structure with a Fe / Si atomic ratio greater than or equal to 1 has the easy-to-break property of the α phase structure described in the present application, and can make the second phase present a more dispersed, fine, and uniform distribution state during the material processing, which is beneficial to improve the strength and elongation of the aluminum foil.
[0102] In some embodiments, the composition of the smelting raw material is as follows: based on the total weight of the smelting raw material, the content of Si is 0.267wt% to 0.54wt%.
[0103] In any embodiment, the size of at least a portion of the second phase of the aluminum foil is less than 3 μm.
[0104] In any embodiment, the proportion of the second phase below 3 μm in all second phases can be 60-100%, for example 60% to 100%, specifically 80% to 100%. In any embodiment, the proportion of the second phase below 3 μm in all second phases can be 60%, 70%, 80%, 90%, 100% or any range of values therebetween. In any embodiment, the proportion of the second phase below 3 μm in all second phases can be 100%.
[0105] By controlling the Fe content and the Si content within the said range, the second phase in the battery aluminum foil can be more concentratedly presented as a dispersed, fine, and evenly distributed AlFeSi phase structure, thereby dispersing the internal stress of the material and further improving the tensile strength and elongation of the material.
[0106] In some embodiments, the smelting raw material further contains less than or equal to 0.03 wt % Cu based on the total weight of the smelting raw material.
[0107] Copper, as an element contained in aluminum ingots used as raw materials for producing battery aluminum foil, will form a composite second phase with iron, silicon, and aluminum, thereby increasing the size of some second phases in the battery aluminum foil, which is not conducive to improving the elongation. By controlling the Cu content within the above range, the production cost caused by purifying trace Cu elements can be reduced while maintaining the high strength and high elongation of the battery aluminum foil.
[0108] In some embodiments, based on the total weight of the smelting raw material, the smelting raw material further contains 0.015 wt% to 0.05 wt% Ti, and optionally further contains 0.025 wt% to 0.045 wt% Ti.
[0109] By containing the Ti element in the above range in the battery aluminum foil, the elongation of the battery aluminum foil can be further improved.
[0110] In some embodiments, the smelting raw material further contains Mn, Mg and Zn. Based on the total weight of the smelting raw material, the content of Mn is 0<Mn≤0.05wt%, the content of Mg is 0<Mg≤0.05wt%, and the content of Zn is 0<Zn≤0.05wt%.
[0111] Mn, Mg and Zn, as elements contained in aluminum ingots used as raw materials for producing battery aluminum foil, will form a composite second phase with iron, silicon and aluminum, thereby increasing the size of the second phase in the battery aluminum foil, which is not conducive to improving the elongation. By controlling the content of Mn, Mg and Zn within the above range, the production cost caused by purifying trace copper elements can be reduced while maintaining the high strength and high elongation of the battery aluminum foil.
[0112] In some embodiments, the tensile strength of the aluminum foil is 200 MPa-300 MPa, and optionally 230 MPa-300 MPa.
[0113] In some embodiments, the tensile strength of the aluminum foil may be 200 MPa, 201 MPa, 230 MPa, 238 MPa, 250 MPa, 254 MPa, 272 MPa, 293 MPa, 300 MPa, or any range therebetween.
[0114] In some embodiments, the elongation at break of the aluminum foil is 3.2%-10%, and optionally 4%-7%.
[0115] In some embodiments, the elongation at break of the aluminum foil may be 3.2%, 4%, 4.30%, 5%, 5.20%, 5.24%, 5.60%, 6%, 6.45%, 7%, 8%, 9%, 10% or any range therebetween.
[0116] The tensile strength of the aluminum foil can be tested in a manner known in the art. As an example, an Instron tensile tester (INSTRON 3343) is used to stretch a rectangular battery aluminum foil sample with a length of 150 mm, a width of 15 mm, and a thickness of 0.013 mm at a stretching speed of 5 mm / min under a gauge length of 50 mm, and the tensile curve is measured. The maximum tensile force in the tensile curve is used as the tensile strength of the battery aluminum foil, and the ratio of the elongation at the time of tensile fracture divided by the length before stretching is used as the elongation at fracture; each sample is measured 6 times in parallel, and the average value is calculated as the tensile strength and elongation at fracture of the sample.
[0117] The aluminum foil has both good tensile strength and excellent elongation at break. Using it as a current collector can effectively improve the flexibility of the pole piece and reduce the probability of brittle fracture of the pole piece, providing a material basis for improving the compaction density of the pole piece and the energy efficiency of the battery.
[0118] In some embodiments, the manufacturing method includes a cold rolling process, and the cold rolling process has no intermediate annealing process.
[0119] Generally, in the manufacturing process of battery aluminum foil, the component segregation generated in the casting process can be alleviated by performing an annealing process on the material, so that the internal composition of the material is more uniform. In the embodiment of the present application, by making the thickness of the battery aluminum foil within the above range, the aluminum foil is thinner, and even without annealing, the uneven composition in the material can be reduced, so that the obtained battery aluminum foil can achieve high strength and high elongation.
[0120] In some embodiments, the method for manufacturing the battery aluminum foil comprises the following steps:
[0121] I. Melting process: When the temperature of the aluminum alloy melt reaches 710℃~740℃, refining and slag removal, grain refinement, degassing and slag removal, and filtration are carried out to obtain an aluminum alloy melt.
[0122] II. Casting step, the filtered aluminum alloy melt is put into a casting and rolling mill to cast and roll into a cast billet;
[0123] III. a cold rolling step of cold rolling the cast billet;
[0124] IV. trimming process to obtain aluminum foil blank;
[0125] V. Foil rolling process, rolling the aluminum foil blanks into aluminum foil coils;
[0126] VI. Aluminum foil slitting process, slitting the aluminum foil roll to obtain battery aluminum foil.
[0127] In some embodiments, the method for manufacturing battery aluminum foil, wherein, in the casting and rolling process, the filtered aluminum alloy melt is put into a casting and rolling machine for continuous casting and rolling into a cast-rolled billet of, for example, 5 mm to 9 mm, optionally 6 mm to 7 mm. In the cold rolling process, the cast-rolled billet is cold rolled until the thickness is, for example, 0.15 mm to 0.3 mm, optionally 0.2 mm to 0.25 mm, and the number of cold rolling passes is, for example, 3-6 times, preferably 5 times. In the trimming process, trimming can be performed at a thickness of, for example, 0.8 mm to 1.5 mm and / or a thickness of 0.2 mm to 0.25 mm to obtain an aluminum foil billet. In the foil rolling process, the trimmed aluminum foil blank is subjected to rough rolling, intermediate rolling and finish rolling in sequence to form an aluminum foil coil with a thickness of 0.01mm to 0.02mm, optionally 0.01mm to 0.015mm. The number of rolling passes is not particularly limited, and can be selected as a total of 5-9 passes, and can further be selected as 6 to 7 passes.
[0128] The battery aluminum foil obtained by the manufacturing method of the present invention has a high α-phase content in the second phase, presenting a more dispersed, fine and uniform distribution state, thereby being able to disperse the internal stress of the material and improve the tensile strength and elongation of the material; in addition, the pinholes of the obtained battery aluminum foil reach the level of general battery foil, which can effectively improve the brittleness of the battery pole piece when used in secondary batteries and improve the wrinkle resistance of the battery aluminum foil.
[0129] In addition, according to the manufacturing method of the present invention, even if the annealing treatment is not performed, the remelting of the second phase in the battery aluminum foil material caused by the annealing treatment can be prevented, thereby causing the reduction of the α-phase structure in the second phase, thereby causing the strength and elongation of the battery aluminum foil material to decrease. In addition, since no annealing treatment is performed, the manufacturing method of the present invention has the advantages of short process flow, high production efficiency, low energy consumption, and low cost. Not only that, the battery aluminum foil of the present application can effectively improve the brittleness of the battery pole piece and improve the wrinkle resistance of the aluminum foil when used in secondary batteries.
[0130] [Battery Electrode]
[0131] In one embodiment of the present application, a battery electrode is provided, which comprises the battery aluminum foil of the present application. The electrode can be selected as a positive electrode.
[0132] The battery electrode has improved brittleness and can achieve a higher ultimate compaction density, which is beneficial to further improve the battery energy density.
[0133] In some embodiments, the compacted density of the battery electrode is 3.5 g / cm 3 When the battery electrode is bent an average number of times is greater than or equal to 3 times.
[0134] In some embodiments, the compacted density of the battery electrode is 3.5 g / cm 3 When the battery electrode is bent an average of 3 to 6 times.
[0135] In some embodiments, the compacted density of the battery electrode is 3.5 g / cm 3 The average bending times of the battery electrodes can be selected as 3, 4, 5 or 6 times.
[0136] For pole pieces with a specific compaction density, the average number of bends can be used to characterize the flexibility of the battery electrode. The higher the average number of bends of the battery electrode, the better the flexibility of the battery electrode, and the less likely the battery electrode is to break brittlely, which is conducive to further improving the compaction density of the battery electrode and further improving the battery energy density.
[0137] The average bending times of the battery electrode can be tested by any method in the art. As an example, the positive electrode sheet is cut into a test sample of 15cm×2.5cm size for later use. Bend the electrode sheet and fold it in half and fix it, and use a 2kg rolling roller to roll it once to check whether there is light transmission or fracture at the fold of the battery electrode; if there is no light transmission or fracture, fold the electrode in half and fix it, and use a 2kg rolling roller to roll it once to check whether there is light transmission or fracture at the fold of the electrode. Repeat the above steps until there is light transmission or fracture at the fold of the electrode, record the number of times the electrode is rolled, take ten samples for this test, and take the average value.
[0138] In some embodiments, when the compaction density of the battery electrode is 3.5 g / cm3, the elongation at break of the battery electrode is greater than 2.1%.
[0139] In some embodiments, when the compaction density of the battery electrode is 3.5 g / cm3, the elongation at break of the battery electrode is 2.1%-6%.
[0140] In some embodiments, when the compaction density of the battery electrode is 3.5 g / cm3, the elongation at break of the battery electrode may be 2.1%, 2.5%, 3%, 4%, 5%, 6% or any range therebetween.
[0141] [Secondary battery]
[0142] In one embodiment of the present application, a secondary battery is provided, which includes the battery electrode.
[0143] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0144] [Positive electrode]
[0145] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application, and the current collector is the battery aluminum foil of the present application. When the battery aluminum foil of the present application is used in a secondary battery, it can effectively improve the brittleness of the battery sheet and improve the wrinkle resistance of the aluminum foil.
[0146] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, the battery aluminum foil of the present application is used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming the battery aluminum foil of the present application on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0147] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO 2 ), lithium nickel oxide (such as LiNiO 2 ), lithium manganese oxide (such as LiMnO 2 、LiMn 2 O 4 ), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (Also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3O 2 (Also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O 2 (Also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O 2 (Also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O 2 (Also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O 2 ) and its modified compounds, etc. Examples of lithium phosphates containing olivine structures may include, but are not limited to, lithium iron phosphate (such as LiFePO 4 (also referred to as LFP), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO 4 ), at least one of a composite material of lithium manganese phosphate and carbon, a composite material of lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0148] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0149] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0150] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0151] [Negative electrode]
[0152] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0153] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0154] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0155] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0156] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0157] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0158] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0159] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0160] [Electrolytes]
[0161] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0162] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0163] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0164] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0165] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0166] [Isolation film]
[0167] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0168] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0169] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0170] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0171] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0172] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 3 The secondary battery 5 is a square structure as an example.
[0173] In some embodiments, reference Figure 4 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the sodium secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0174] In some embodiments, the sodium secondary batteries can be assembled into a battery module. The number of sodium secondary batteries contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0175] Figure 5 4 is an example of a battery module. Figure 5 In the battery module 4, the plurality of sodium secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of sodium secondary batteries 5 may be fixed by fasteners.
[0176] Optionally, the battery module 4 may further include a housing having a housing space, and the plurality of sodium secondary batteries 5 are housed in the housing space.
[0177] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0178] Figure 6 and Figure 7 1 is a battery pack 1 as an example. Figure 6 and Figure 7 The battery pack 1 may include a battery box and a plurality of battery modules 6 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0179] In addition, the present application also provides an electrical device, which includes at least one of the sodium secondary battery, battery module, or battery pack provided in the present application. The sodium secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0180] As an electrical device, a sodium secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0181] Figure 8 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the power consumption device's requirements for high power and high energy density of sodium secondary batteries, a battery pack or a battery module can be used.
[0182] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a sodium secondary battery may be used as a power source.
[0183] Example
[0184] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0185] Example 1
[0186] (1) Preparation of aluminum foil
[0187] Prepare smelting formula: Aluminum ingot, AlFe master alloy, AlSi master alloy and AlCu master alloy are mixed in a certain weight ratio to obtain a smelting formula, in which the weight percentage of each element is: Fe: 0.525, Si: 0.4, Cu: 0.01, Ti: 0.015, Mn: 0.05, Mg: 0.05, Zn: 0.05, and the rest is Al and unavoidable impurities. Among them, the above-mentioned Cu, Mn, Mg and Zn all come from aluminum ingots.
[0188] Melting: put the above smelting formula into the smelting furnace for heating and smelting, and set the furnace gas temperature to 1000℃; when the metal is melted and the temperature of the aluminum alloy melt reaches 730℃, carry out refining and slag removal, holding furnace refining, degassing and deslagging, and filtering treatment in sequence;
[0189] Casting and rolling: the filtered aluminum alloy melt is fed into a casting and rolling mill through a flow channel and continuously cast and rolled into a 6.0-7 mm cast and rolling billet;
[0190] Cold rolling: The billet is cold rolled to 0.22 mm in 5 passes;
[0191] Edge trimming: Edge trimming is performed once at a thickness of 0.8-1.5 mm and once at a thickness of 0.22 mm;
[0192] Foil rolling: The trimmed aluminum foil billet is subjected to six passes of rough rolling, intermediate rolling and finish rolling to form an aluminum foil coil with a thickness of 0.013 mm;
[0193] Slitting: Slitting the above aluminum foil rolls can obtain finished high-performance aluminum foil for batteries.
[0194] The electron microscope image of the battery aluminum foil obtained above is shown in the attached Figure 1 As shown, Figure 1 The light-colored part is the second phase in the battery aluminum foil, which contains α, β and θ phases, among which the content of α phase is increased, and the second phase structure presents a dispersed structure.
[0195] In addition, the tensile strength and elongation of the battery aluminum foil of Example 1 were tested by the tensile strength and elongation test method described later, and 6 groups were measured in parallel. The tensile strength value was used as the vertical axis and the elongation value was used as the horizontal axis to fit the curve, as shown in FIG. Figure 2 shown.
[0196] (2) Preparation of batteries
[0197] The positive electrode active material NCM811, the conductive agent carbon black, and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97:1:2 in an N-methylpyrrolidone (NMP) solution to prepare a positive electrode slurry, which is then coated on the surface of the prepared aluminum foil using an extrusion coater and dried to obtain a positive electrode film layer. The coated electrode is then cold-pressed by a cold press to prepare the final positive electrode electrode. The surface density of the single-sided film layer of the positive electrode electrode is 350mg / 1540.25mm 2 ; The compaction density of the positive electrode is 3.5g / cm 3 .
[0198] Example 2
[0199] The contents of Fe and Si in the battery aluminum foil were changed as shown in Table 1, and the rest was carried out in the same manner as in Example 1 to obtain a battery aluminum foil, which was then tested as follows.
[0200] Example 3
[0201] The contents of Fe and Si in the battery aluminum foil were changed as shown in Table 1, and the rest was carried out in the same manner as in Example 1 to obtain a battery aluminum foil, which was then tested as follows.
[0202] Example 4
[0203] The Cu content in the battery aluminum foil was changed as shown in Table 1, and the rest was carried out in the same manner as in Example 1 to obtain a battery aluminum foil, which was then tested as follows.
[0204] Example 5
[0205] The Ti content in the battery aluminum foil was changed as shown in Table 1, and the rest was carried out in the same manner as in Example 1 to obtain a battery aluminum foil, which was then tested as follows.
[0206] Example 6
[0207] A battery aluminum foil was manufactured according to the raw material ratio of Example 1, and an intermediate annealing process was performed during the manufacturing process. The rest was carried out in the same manner as Example 1 to obtain a battery aluminum foil, which was then tested as follows.
[0208] Comparative Example 1
[0209] The contents of Fe and Si in the battery aluminum foil were changed as shown in Table 1 so that the Fe / Si ratio was 2.47. The rest was carried out in the same manner as in Example 1 to obtain a battery aluminum foil, which was then tested as follows.
[0210] Comparative Example 2
[0211] The contents of Fe and Si in the battery aluminum foil were changed as shown in Table 1 so that the Fe / Si ratio was 0.61. The rest was carried out in the same manner as in Example 1 to obtain a battery aluminum foil, which was then tested as follows.
[0212] (1) Performance test of battery aluminum foil
[0213] Tensile strength and elongation at break test
[0214] A rectangular battery aluminum foil strip with a length of 150 mm, a width of 15 mm, and a thickness of 0.013 mm was stretched at a stretching speed of 5 mm / min under a gauge length of 50 mm using an Instron tensile testing machine (INSTRON 3343). The tensile curve was measured, and the tensile strength of the battery aluminum foil was calculated using the maximum tensile force in the tensile curve. The elongation at break was taken as the ratio of the elongation at break divided by the length before stretching. Each sample was measured 6 times in parallel, and the average value was calculated as the tensile strength and elongation at break of the sample.
[0215] Test of the elongation at break of the pole piece
[0216] An Instron tensile testing machine (INSTRON 3343) was used to stretch a positive electrode sheet sample with a length of 150 mm and a width of 15 mm at a stretching speed of 5 mm / min under a gauge length of 50 mm. The tensile curve was measured, and the maximum tensile force in the tensile curve was used to calculate the tensile strength of the battery aluminum foil. The ratio of the elongation at break divided by the length before stretching was used as the elongation at break. Each sample was measured 6 times in parallel, and the average value was calculated as the tensile strength and elongation at break of the sample.
[0217] Pole brittleness test
[0218] The positive electrode sheet prepared in the embodiment is cut into test samples of 15cm×2.5cm size for later use. Bend the electrode sheet and fold it in half to fix it, and use a 2kg rolling roller to roll it once to check whether there is light transmission or breakage at the fold of the electrode sheet; if there is no light transmission or breakage, fold the electrode sheet in half again and fix it, and use a 2kg rolling roller to roll it once to check whether there is light transmission or breakage at the fold of the electrode sheet, and repeat the above steps until there is light transmission or breakage at the fold of the electrode sheet, record the number of times the electrode sheet is rolled, take ten samples for brittleness test, and take the average value. The relevant parameters and experimental results of the battery aluminum foil of the above embodiment and comparative example are shown in Table 1 below.
[0219] Table 1: Experimental results of embodiments and comparative examples
[0220]
[0221]
[0222] According to the results, the battery aluminum foil obtained in Examples 1 to 6 meets the requirements of the present application in terms of composition and structure, and the tensile strength and elongation are significantly excellent, and good results are achieved; the pole piece has improved flexibility and increased elongation at break. The Mn, Mg and Zn in the test results are all impurities in the raw materials, and their respective contents in the aluminum foil are less than 0.05wt%, which meets the national standards.
[0223] On the other hand, the battery aluminum foil of Example 6 has a decreased tensile strength due to the implementation of an intermediate annealing step during the preparation process, but the elongation is still maintained at a high level, and the overall effect is still good.
[0224] In contrast, in Comparative Examples 1 and 2, the Fe / Si ratio in the battery aluminum foil is too high or too low, and neither falls within the above-mentioned specific range of the present application, and the respective content ranges of Fe and Si are also too low. As a result, the tensile strength and elongation of the obtained battery aluminum foil are significantly worse than those of the embodiments of the present application.
[0225] It should be noted that the present application is not limited to the embodiments described. The embodiments described are only examples, and the embodiments having substantially the same structure as the technical idea and exerting the same effects within the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the subject matter of the present application, other methods of applying various modifications that can be thought of by those skilled in the art to the embodiments and combining some of the constituent elements in the embodiments to construct the embodiments are also included in the scope of the present application.
Claims
1. A battery aluminum foil, characterized in that: Containing Fe and Si, based on the total weight of the aluminum foil, the content of Fe is 0.4wt% to 0.65wt%, the content of Si is 0.25wt% to 0.54wt%, and the weight ratio of Fe to Si (Fe / Si) is 1.2 to 1.
5.
2. The battery aluminum foil according to claim 1, characterized in that: Based on the total weight of the aluminum foil, the content of Si is 0.267 wt % to 0.54 wt %.
3. The battery aluminum foil according to claim 1 or 2, characterized in that: The aluminum foil includes a second phase, and the second phase includes one or more of the following characteristics: (1) The size of at least part of the second phase of the aluminum foil is less than 3 μm; (2) The size of at least part of the second phase of the aluminum foil is less than 3 μm, and at least part of the second phase is dispersed. (3) The second phase of the aluminum foil contains 5wt% to 10wt% of AlFeSi structure and 4wt% to 9wt% of AlFe structure.
4. The battery aluminum foil according to any one of claims 1 to 3, characterized in that: The aluminum foil includes one or more of the following features: (1) Based on the total weight of the aluminum foil, the aluminum foil further contains less than or equal to 0.03 wt % of Cu; (2) Based on the total weight of the aluminum foil, the aluminum foil further contains 0.015 wt% to 0.05 wt% of Ti, and optionally further contains 0.025 wt% to 0.045 wt% of Ti. (3) The aluminum foil further contains Mn, Mg and Zn, and based on the total weight of the aluminum foil, the content of Mn is 0<Mn≤0.05wt%, the content of Mg is 0<Mg≤0.05wt%, and the content of Zn is 0<Zn≤0.05wt%.
5. The battery aluminum foil according to any one of claims 1 to 4, characterized in that: The aluminum foil includes one or more of the following features: (1) The thickness of the aluminum foil is 12 μm to 15 μm; (2) The roughness of the aluminum foil is 0.1 μm to 0.3 μm; (3) The tensile strength of the aluminum foil is 200MPa-300MPa; (4) The tensile strength of the aluminum foil is 230MPa-300MPa; (5) The elongation at break of the aluminum foil is 3.2%-10%; (6) The elongation at break of the aluminum foil is 4%-7%.
6. A method for manufacturing battery aluminum foil, characterized in that: The aluminum foil is formed by heating and melting the smelting raw materials in a smelting furnace according to the ingredient list, and then casting and rolling. The composition of the smelting raw materials is: based on the total weight of the smelting raw materials, The content of Fe is 0.4wt% to 0.65wt%, the content of Si is 0.25wt% to 0.54wt%, and the weight ratio of Fe to Si (Fe / Si) is 1.2 to 1.
5.
7. The method for manufacturing battery aluminum foil according to claim 6, characterized in that: The composition of the smelting raw materials includes one or more of the following characteristics: (1) Based on the total weight of the smelting raw materials, the content of Si is 0.267wt% to 0.54wt%; (2) Based on the total weight of the smelting raw material, the smelting raw material further contains less than or equal to 0.03wt% of Cu; (3) Based on the total weight of the smelting raw material, the smelting raw material further contains 0.015wt% to 0.05wt% Ti, and optionally further contains 0.025wt% to 0.045wt% Ti; (4) The smelting raw material further contains Mn, Mg and Zn. Based on the total weight of the smelting raw material, the content of Mn is 0<Mn≤0.05wt%, the content of Mg is 0<Mg≤0.05wt%, and the content of Zn is 0<Zn≤0.05wt%. 8 . The method for producing a battery aluminum foil according to claim 6 , wherein the method comprises an intermediate annealing step or does not comprise an intermediate annealing step.
9. The method for producing a battery aluminum foil according to any one of claims 6 to 8, comprising the following steps: I. Melting process: When the temperature of the aluminum alloy melt reaches 710℃~740℃, refining and slag removal, grain refinement, degassing and slag removal, and filtration are carried out to obtain an aluminum alloy melt. II. Casting step, the filtered aluminum alloy melt is put into a casting and rolling mill to cast and roll into a cast billet; III. a cold rolling step of cold rolling the cast billet; IV. trimming process to obtain aluminum foil blank; V. Foil rolling process, rolling the aluminum foil blanks into aluminum foil coils; VI. Aluminum foil slitting process, slitting the aluminum foil roll to obtain battery aluminum foil.
10. A battery pole piece, characterized in that: A battery aluminum foil comprising the battery aluminum foil according to any one of claims 1 to 5.
11. The battery pole piece according to claim 10, characterized in that: The compaction density of the battery electrode is 3.5 g / cm 3 The bending times of the battery electrode sheet are greater than or equal to 3 times; the bending times of the battery electrode sheet are tested by rolling method, the battery electrode sheet is cut into test specimens of 15 cm × 2.5 cm in size, and a 2 kg rolling roller is used to roll the bent and folded electrode sheet. If there is no light transmission or fracture at the bending part of the electrode sheet, the electrode sheet is folded in reverse and rolled, and the number of rolling times at which light transmission or fracture appears at the folded part of the electrode sheet is taken as the bending times of the battery electrode sheet.
12. The battery pole piece according to claim 10 or 11, characterized in that: The compaction density of the battery electrode is 3.5 g / cm 3 When the battery electrode has a fracture elongation greater than 2.1%. 13 . A secondary battery comprising the battery electrode according to claim 10 .
14. An electric device comprising the secondary battery according to claim 13.